Status, characterization, and potential utilization of municipal solid waste as renewable energy source: Lahore case study in Pakistan. (January 2020) - Azam, Mudassar; Jahromy, Saman Setoodeh; Raza, Waseem; Raza, Nadeem; Lee, Sang Soo; Kim, Ki-Hyun; Winter, Franz
Highlights: Uncontrolled municipal solid waste (MSW) is a threat to public health and environmental safety. Waste to Energy program would be beneficial for waste management plan. The incineration of 2000 tons Lahore MSW/day has an energy recovery potential of 80 MW. Good strategies for waste management should be set for diverse industrial source processes. Abstract: With rapid increases in population and urbanization, uncontrolled municipal solid waste (MSW) is a threat to public health and environmental safety. In this study, we explore its generation, treatment, and characteristics of physical/chemical composition and assess the potential of MSW as a renewable energy source in Lahore, the second largest city in Pakistan. Based on the average generation rate of MSW ( i.e., 0.65 kg/capita/day), the daily production of MSW in this city would reach 7150 tons/day. However, its disposal in a safely engineered way has been restricted due to the lack of: (a) pre-planning, (b) infrastructure, (c) political will, and (d) public awareness. Various samples of MSW considering socio-economic structure were collected. The physical components of MSW in Lahore were found to be in the descending order of biodegradable, nylon plastic bags, textile, diaper, and paper. The inductively coupled plasma optical emission spectroscopy (ICP-OES) technique was used to determine the heavy metal content and leachability of the MSW components to check for the environmental contamination risk. The proximate and ultimate analysis of this MSW was also carried out along with its heating values. The average high heating value of MSW was measured as 14, 490 kJ kg −1 . Energy recovery potential of 48 MW was assessed further from 2000 tons of MSW/day. The results of this study should be helpful for policy makers to establish a MSW management strategy for the potential renewable energy alternative.